ANALISIS VIKTIMISASI STRUKTURAL TERHADAP TIGA KORBAN PERDAGANGAN PEREMPUAN DAN ANAK PEREMPUAN - Annisa Jihan Andari (Jurnal Kriminologi Indonesia, 2011)
This article discussed the victimization of women and girls through human trafficking. The research sees the interplay of structural factors in the society, including economic factors, social factors, and ideological factors have created vulnerability to women and girls. Such vulnerability has victimized and pushed the women and girls into human trafficking. Thus, the victimization may be regarded as a structural victimization. The research framework is based on literature reviews and conceptual definitions. This research uses qualitative method and involves three victims of trafficking as its subjects, and analyzes their life narrations.